Utility of linear mixed effects models for event-related potential research with infants and children - Heise, Megan J.; Mon, Serena K.; Bowman, Lindsay C. (Developmental cognitive neuroscience, 2022)
Event-related potentials (ERPs) are advantageous for investigating cognitive development. However, their application in infants/children is challenging given children’s difficulty in sitting through the multiple trials required in an ERP task. Thus, a large problem in developmental ERP research is high subject exclusion due to too few analyzable trials. Common analytic approaches (that involve averaging trials within subjects and excluding subjects with too few trials, as in ANOVA and linear regression) work around this problem, but do not mitigate it. Moreover, these practices can lead to inaccuracies in measuring neural signals. The greater the subject exclusion, the more problematic inaccuracies can be. We review recent developmental ERP studies to illustrate the prevalence of these issues. Critically, we demonstrate an alternative approach to ERP analysis—linear mixed effects (LME) modeling—which offers unique utility in developmental ERP research. We demonstrate with simulated and real ERP data from preschool children that commonly employed ANOVAs yield biased results that become more biased as subject exclusion increases. In contrast, LME models yield accurate, unbiased results even when subjects have low trial-counts, and are better able to detect real condition differences. We include tutorials and example code to facilitate LME analyses in future ERP research. •Linear Mixed Effects models (LMEs) have advantages for event-related potential analyses.•For infant/child ERPs especially, LME is superior to traditional ANOVA models.•In simulated ERP data, ANOVAs returned biased results, but LME was unbiased.•In real, child ERP data, LME detected condition differences where ANOVA did not.•Tutorial and sample codes given to guide use of LMEs in future research.